2021
DOI: 10.1186/s13722-021-00219-9
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarettes’ withdrawal severity symptoms among users during intermittent fasting: a cross-sectional study

Abstract: Background Recently, electronic cigarette (e-cig) usage has increased significantly, making it a potentially effective smoking cessation tool. In Muslim countries, most people who use e-cigarettes fast the month of Ramadan, which results in intermittent fasting. This study aims to reveal the severity of e-cig withdrawal symptoms among users during this intermittent fasting period. Methods A self-administered survey was developed and validated to so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Moreover, EC as a novel smoking method is gaining popularity worldwide due to its appealing flavors and the commercial claims of their benefits as a smoking cessation tool, despite the controversial scientific evidence. 72 - 75 In Jordan, EC use is increasing as the government has recently legalized the importation, distribution, and sale of EC in various retail stores in the country. 72 , 74 , 76 In a national survey that was conducted in 2019 in Jordan, and among the 1820 participants involved, the prevalence of exclusive EC use and dual-use was estimated to be 11.7%, and 4.0%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, EC as a novel smoking method is gaining popularity worldwide due to its appealing flavors and the commercial claims of their benefits as a smoking cessation tool, despite the controversial scientific evidence. 72 - 75 In Jordan, EC use is increasing as the government has recently legalized the importation, distribution, and sale of EC in various retail stores in the country. 72 , 74 , 76 In a national survey that was conducted in 2019 in Jordan, and among the 1820 participants involved, the prevalence of exclusive EC use and dual-use was estimated to be 11.7%, and 4.0%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 72 - 75 In Jordan, EC use is increasing as the government has recently legalized the importation, distribution, and sale of EC in various retail stores in the country. 72 , 74 , 76 In a national survey that was conducted in 2019 in Jordan, and among the 1820 participants involved, the prevalence of exclusive EC use and dual-use was estimated to be 11.7%, and 4.0%, respectively. 77 Another recent online cross-sectional survey in Jordan that included 1536 participants found that around 18% of the study sample were EC users, and its usage was more prominent among males and young age groups.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of e-cig withdrawal symptoms among users during RF was evaluated using a self-administered survey developed and validated to solicit anonymous responses from e-cig users in Jordan through a cross-sectional study ( n = 523; 96.4% males; 86.4% aged between 18 and 40 years). 87 Severity scores of physical and psychological withdrawal symptoms were assessed and calculated. Many participants replaced tobacco smoking with e-cig (53.5%) to help them stop smoking.…”
Section: Highlights Of the Year's Literaturementioning
confidence: 99%
“…Some studies claimed that ENDS can help smokers to change their smoking habits. As an alternative to cigarettes, ENDS may relieve smokers from experiencing withdrawal symptoms and provide them with more choices ( 40 ). Smokers can switch to e-liquid products with different flavors and have a better quitting experience ( 41 ).…”
Section: Discussionmentioning
confidence: 99%